LITERASI MATEMATIKA CALON GURU SEKOLAH DASAR DALAM MENYELESAIKAN MASALAH PISA KONTEN SHAPE AND SPACE - Vivi Rachmatul Hidayati; Nourma Pramestie Wulandari; Mohammad Archi Maulyda; Muhammad Erfan; Awal Nur Kholifatur Rosyidah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
Mathematical literacy is an ability that is needed by students in this changing era. Mathematical literacy can be seen from the ability to formulate contextual problems mathematically; using facts, concepts, and mathematical procedures; as well as interpreting and evaluating mathematical outcomes well. One of the factors that cause students' good mathematical literacy is teacher's good mathematics literacy. The purpose of this study is to describe the mathematical literacy abilities of pre-service elementary school teacher in solving PISA problems about shape and space. This research method is qualitative-descriptive. The subjects of the study were pre-service elementary school teachers, each with high, medium, and low cognitive abilities. The results showed that high-ability pre-service teacher were able to demonstrate good mathematical literacy performance, which was able to fulfil all three aspects namely formulating mathematical problems; use mathematical concepts and procedures well; and interpret mathematical answers well in the context of the problem. Medium-ability pre-service teachers are not able to meet several indicators on aspects of formulating problems and using mathematical concepts and procedures. Low-ability pre-service teachers cannot fulfil all indicators on aspects of using mathematical concepts and procedures properly.